Pengaruh Penambahan Presentase Serbuk Kaca pada Karakteristik Beton Terhadap Nilai Slump - Fadilla, Deska Vira; Trimurtiningrum, Retno; Sutriono, Bantot; Rochmah, Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Concrete is the most commonly used construction material in the construction industry. Concrete has properties that are resistant to high pressure and extreme temperatures which allows wide use and according to needs. In this research, additional materials were used from glass waste which was processed into glass powder that passed through sieve No. 200. To find out additional characteristics, one of them is to know the effect of the slump value which is planned in accordance with SNI 03 – 2834 – 2000. This research uses the DOE (Department of Environment) method. The results of this research show that the average slump value of concrete aged 7 days, 14 days, and 28 days using glass powder percentages of 0%, 4.5%, 6.5% , 8.5%, and 10.5% are 12 cm, 12 cm, 10.33 cm, 9.83 cm, and 9.33 cm.